Assistant effect of poly(methyl methacrylate)-grafted carbon nanotubes on the beta polymorph of poly(vinylidene fluoride) during microinjection1. Issue 67 (24th July 2015) - Bai, Feng; Chen, Gang; Nie, Min; Wang, Qi
<x xml:space="preserve">Abstract</x> A facial way to fabricate an electroactive PVDF device directly through melt processing.